2013
DOI: 10.1002/ece3.513
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic climate change and diversification on the continental shelf and slope: evolution of gastropod diversity in the family Solariellidae (Trochoidea)

Abstract: Recent expeditions have revealed high levels of biodiversity in the tropical deep-sea, yet little is known about the age or origin of this biodiversity, and large-scale molecular studies are still few in number. In this study, we had access to the largest number of solariellid gastropods ever collected for molecular studies, including many rare and unusual taxa. We used a Bayesian chronogram of these deep-sea gastropods (1) to test the hypothesis that deep-water communities arose onshore, (2) to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(98 citation statements)
references
References 117 publications
(245 reference statements)
10
87
0
Order By: Relevance
“…Debates have focused on the impact of variations in temperature, oxygenation and circulation mode on the colonization of deep habitats, and at least for the late Cenozoic, deep-sea sediment cores have provided extensive benthic foraminifer and ostracod microfossil evidence in this respect [3,4]. Biogeographic patterns and molecular clock estimates have yielded dates which predominantly converge to a latest Mesozoic or early Cenozoic origin of the modern deep-sea fauna [5][6][7][8][9]. Testing these hypotheses and exploring older deep-sea biodiversity using direct fossil evidence, however, has been hampered so far by the sparse record of & 2014 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…Debates have focused on the impact of variations in temperature, oxygenation and circulation mode on the colonization of deep habitats, and at least for the late Cenozoic, deep-sea sediment cores have provided extensive benthic foraminifer and ostracod microfossil evidence in this respect [3,4]. Biogeographic patterns and molecular clock estimates have yielded dates which predominantly converge to a latest Mesozoic or early Cenozoic origin of the modern deep-sea fauna [5][6][7][8][9]. Testing these hypotheses and exploring older deep-sea biodiversity using direct fossil evidence, however, has been hampered so far by the sparse record of & 2014 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…Solariellidae is a family of small marine vetigastropods found worldwide from littoral to abyssal depths, and eye loss has been reported in several species across the family (Marshall ; Williams et al. ). This group provides an excellent opportunity to study the potential for anatomical determinism in eye loss and to draw comparisons among eyeless taxa, and offers a larger sample of eye reduction events than more commonly studied cavernicolous groups (Jeffery ; Tierney et al.…”
mentioning
confidence: 99%
“…Kensley, 1973 Notes. Molecular sequence data has demonstrated that the material studied by and Herbert (1987c) is composite, containing at least one additional cryptic species (Williams et al 2013). Further studies are needed to resolve the taxonomy of this complex.…”
Section: -New Combinationmentioning
confidence: 99%
“…At that time, however, the solariellid fauna of the central Indo-West Pacific was little known and, erring on the side of caution, I was reluctant to definitively conclude that Margarita bicarinata was in fact a South African rather than an oriental species. In the intervening years the solariellid fauna the 'Eastern Seas' has become better documented Poppe & Tagaro 2008c;Vilvens 2009;Williams et al 2013;Vilvens, Williams & Herbert 2014;Vilvens & Williams in press), but no species resembling Margarita bicarinata has been encountered. As a result, I believe it can be justifiably concluded that Margarita bicarinata was originally mislocalised and that it is in fact the Agulhas Bank taxon currently known by the name Ilanga undata undata.…”
Section: -New Combinationmentioning
confidence: 99%
See 1 more Smart Citation